The curriculum planning and implementation for mindfulness education and diversified humanism based on big data - Xiaolin Li (Scientific Reports)
Abstract In modern education, balancing academic achievement and personal development is crucial. Traditional methods often focus more on academics, neglecting personal and social skills. To address this, the study combines mindfulness education with humanistic theory to improve curriculum design. Mindfulness education emphasizes attention control, self-awareness, and emotional management. Humanistic theory focuses on student-centered learning, creativity, and self-fulfillment. This study uses quantitative research to compare different teaching methods. The research findings show that traditional teaching methods, while effective in improving students’ academic performance, have limited impact on the development of their personal and social skills. In contrast, the optimized curriculum not only significantly increases students’ classroom participation and interest in learning but also greatly enhances their self-confidence, sense of responsibility, teamwork, and creativity. Particularly in terms of focus and empathy, students made more noticeable progress. This indicates that the optimized curriculum helps improve students’ self-awareness, emotional management, and collaborative skills. Overall, the study highlights the potential of comprehensive curriculum planning in promoting students’ holistic development and emphasizes the importance of student-centered teaching approaches in cultivating learners with more integrated qualities.